TOXOPLASMOSE: UMA BREVE REVISÃO - dos Santos, Camila Alves; Bertolini, Andressa; Simon, Micely da Fonseca; Marschall, Alisson Diel; Alves, Bruna Farias; Lusa, Tatiane; Wurfel, Simone de Fátima Rauber (Anais de Medicina Veterinária, 2022)
.